PENERAPAN VALUE CLARIFICATION TECHNIQUE (VCT) MODEL ROLE PLAYING DALAM MATA PELAJARAN IPS UNTUK MENEKAN PERILAKU BULLYING SISWA DI SMP NEGERI 4 BANDUNG - Wiradimadja, Agung Wiradimadja (JURNAL PENDIDIKAN ILMU SOSIAL, 2016)
This research was motivated by the concern over student’s delinquency phenomenon, especially bullying that have been widespread in education. Like a vicious circle, if bullying was not stopped it’s more likely being passed from one generation to others among the victims. Special handling needed in order to break the bullying chain. Based on preliminary observations in SMP Negeri 4 Bandung, some bullying behaviors were visibly done by the students of class VIII - E. Based on the data collected, bullying behavior by students of class VIII - E were quite high, therefore a learning strategy should be formulated in social studies to reduce bullying. The approach used in this study was class activity observation by adopted VCT model of role playing in social science learning implementation. The instrument used was a student’s bullying behavior observational sheet and student’s social science learning activities field note. Data collection techniques being used were observation, documentation studies and interview, while for the data processing and analysis qualitative and quantitative technique were used. Based on the final research being done, first the implementation started by determined the competency standards and basic competencies in order to arrange the lesson plan being used, second VCT role-playing model was implemented in the social science learning process in the classroom, third the result of the research during the class activities shown that bullying behavior of the students in 1st cycle up to the 3rd cycle were decreased, forth the obstacles from each cycle was reflected, fifth some efforts given to overcome the obstacles appeared from each cycle. Conclusion from the research was, the maximum result achieved in decreasing bullying behavior was in the 3rd cycle.Keyword: Bullying, Value Clarification Technique (VCT).